2022
DOI: 10.1007/s10346-022-01913-8
|View full text |Cite
|
Sign up to set email alerts
|

A new method to detect changes in displacement rates of slow-moving landslides using InSAR time series

Abstract: Slow-moving landslides move downslope at velocities that range from mm year−1 to m year−1. Such deformations can be measured using satellite-based synthetic aperture radar interferometry (InSAR). We developed a new method to systematically detect and quantify accelerations and decelerations of slowly deforming areas using InSAR displacement time series. The displacement time series are filtered using an outlier detector and subsequently piecewise linear functions are fitted to identify changes in the displacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 81 publications
2
2
0
Order By: Relevance
“…The average subsidence rate of MPs within this cluster was −4.9 cm/y, with a maximum rate of −10 cm/y. This coincides with previous studies, which observed an extensive subsidence feature encompassing the area of Margaarish Town, Bandung City with displacement rates of −10 cm/yr to −2 cm/yr between 2014 to 2017 [62]. Another study, which used Sentinel-1 and ALOS-2 images acquired from September 2014 to July 2017, found that the mean velocity of this subsidence centre was −11.2 cm/y, covering an area of 14.3 km 2 [67].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The average subsidence rate of MPs within this cluster was −4.9 cm/y, with a maximum rate of −10 cm/y. This coincides with previous studies, which observed an extensive subsidence feature encompassing the area of Margaarish Town, Bandung City with displacement rates of −10 cm/yr to −2 cm/yr between 2014 to 2017 [62]. Another study, which used Sentinel-1 and ALOS-2 images acquired from September 2014 to July 2017, found that the mean velocity of this subsidence centre was −11.2 cm/y, covering an area of 14.3 km 2 [67].…”
Section: Discussionsupporting
confidence: 93%
“…The re-referenced displacement pattern remains similar to the un-corrected map (Figure 5c); however, the range of velocity values have changed and now reflect more realistic displacement estimates with a maximum subsidence rate of −18.7 cm/y and an uplift rate of 2.3 cm/y, which is more or less stable given that the standard deviation for the re-referenced InSAR velocity results is 3.1 cm/y. These values are more in line with previous InSAR results [62][63][64].…”
supporting
confidence: 93%
See 1 more Smart Citation
“…A-DInSAR, on the other hand, made it possible to analyze and monitor the areas in proximity to the cliffs and the potential presence of slow-moving phenomena in the gently dipping slopes on the northwest side of the towns. The A-DInSAR technique is a well-known approach used to detect and monitor slow-moving landslides [57][58][59]. However, rockfalls are characterized by rapid and very rapid velocities [60], decreasing the applicability of this technique to these phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Landsat, ALOS, Quick Bird, and other satellites with high-resolution images have been widely used for landslide identification; however, they only identify landslide hazards with clear deformation (McDonald and Grubbs, 1975;Sato and Harp, 2009;Youssef et al, 2009;García-Davalillo et al, 2014). InSAR with centimeter-high precision and all-weather surface observation technology can perform large-scale landslide identification and monitoring to build a landslide hazard inventory (Woods et al, 2020;Urgilez Vinueza et al, 2022;Zhang et al, 2022). Because of the satellite lateral imaging mode, the terrain may cause geometric distortion of SAR images, including perspective shortening, overlap, and shadow (Jie et al, 2018).…”
mentioning
confidence: 99%